Eco‐Mn Ecocatalysts: Toolbox for Sustainable and Green Lewis Acid Catalysis and Oxidation Reactions. Issue 6 (7th January 2020) - Bihanic, Camille; Richards, Kenza; Olszewski, Tomasz K.; Grison, Claude
Abstract: Phytoextraction is one of the most promising phytotechnologies used to restore natural environments degraded by mining activities. In New Caledonia, a few plant species, which belong to the Grevillea genus, have the ability to extract Mn from soil and accumulate it in abundance (over 1 % of leaves dry weight). This review describes the use of Grevillea Mn‐accumulating plant species to produce the first bio‐sourced Mn catalysts, called Eco‐Mn catalysts. Extensive structural studies of Eco‐Mn catalysts have highlighted an original composition characteristic of their vegetal origin. Eco‐Mn catalysts have demonstrated competitive catalytic activities compared to conventional Mn catalysts in Lewis acid catalysis, aminoreductions, alcohol oxidations, epoxidation reactions, oxidative cleavage of 1, 2‐diols and alkenes and "Janus catalysts" for sequential tandem oxidations such as tandem carbonyl‐ene cyclisation, synthesis of substituted pyridines and oxidative iodination of ketones. Abstract : Ecocatalysis : This review describes the use of Grevillea Mn‐accumulating plant species to produce the first bio‐sourced Mn catalysts, called Eco‐Mn catalysts. Extensive structural studies of Eco‐Mn catalysts have highlighted an original composition characteristic of their vegetal origin. Eco‐Mn catalysts have demonstrated competitive catalytic activities compared to conventional Mn catalysts in Lewis acid catalysis, aminoreductions, alcohol oxidations, epoxidation reactions, oxidative cleavage of 1, 2‐diols and alkenes and "Janus catalysts" for sequential tandem oxidations.